2022
DOI: 10.1371/journal.pone.0262731
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a virtual learning environment on the conscious prescription of antibiotics among Colombian dentists

Abstract: Appropriate antibiotic prescription contributes to reducing bacterial resistance; therefore, it is critical to provide training regarding this challenge. The objective of this study was to develop a virtual learning environment for antibiotic prescription and to determine its impact on dentists’ awareness, attitudes, and intention to practice. First, the learning content on multimedia resources was developed and distributed into three challenges that participants had to overcome. Then, a quasi-experimental stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A frequency of at least every 5 years for deploying postgraduate training on antibiotic use would probably represent the minimum educational standard [ 29 ]. A study performed in Colombia showed that a virtual learning environment for antibiotic prescription in dentistry significantly improved the awareness, attitudes, and intention to practice of dentists; however, 6 months after training, this positive effect was still present only for the awareness and intention to practice, while it had been lost for attitudes [ 52 ], suggesting that reinforcement might be required more frequently than the 5 years cited above [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A frequency of at least every 5 years for deploying postgraduate training on antibiotic use would probably represent the minimum educational standard [ 29 ]. A study performed in Colombia showed that a virtual learning environment for antibiotic prescription in dentistry significantly improved the awareness, attitudes, and intention to practice of dentists; however, 6 months after training, this positive effect was still present only for the awareness and intention to practice, while it had been lost for attitudes [ 52 ], suggesting that reinforcement might be required more frequently than the 5 years cited above [ 29 ].…”
Section: Discussionmentioning
confidence: 99%